2012
DOI: 10.1002/chem.201102203
|View full text |Cite
|
Sign up to set email alerts
|

A Disulfide Bridge Allows for Site‐Selective Binding in Liver Bile Acid Binding Protein Thereby Stabilising the Orientation of Key Amino Acid Side Chains

Abstract: The presence of a disulfide bridge in liver bile acid binding protein (L-BABP/S-S) allows for site-selective binding of two bile acids, glycochenodeoxycholic (GCDA) and glycocholic acid (GCA), differing only in the presence of a hydroxyl group. The protein form devoid of the disulfide bridge (L-BABP) binds both bile salts without discriminating ability. We investigate the determinants of the molecular recognition process in the formation of the heterotypic L-BABP/S-S complex with GCDA [corrected] and GCA [corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 37 publications
1
22
0
1
Order By: Relevance
“…The chemical shift changes observed between apo (without ligand) and holo (in the presence of ligand) protein at IRG:BABP ratio of 3 are plotted in Figure A. Residues significantly affected by IRG addition, namely S61, F62, G65, T71, T72, G75, K77, C80, A85, C91, H98, V102, I111, and K123, have been mapped on the BABP structure, previously determined by NMR (Figure B). Key residues involved in binding are located in the strand regions delimiting the protein cavity, at the level of βD‐βJ strands, indicating that IRG is hosted in the protein internal cavity.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical shift changes observed between apo (without ligand) and holo (in the presence of ligand) protein at IRG:BABP ratio of 3 are plotted in Figure A. Residues significantly affected by IRG addition, namely S61, F62, G65, T71, T72, G75, K77, C80, A85, C91, H98, V102, I111, and K123, have been mapped on the BABP structure, previously determined by NMR (Figure B). Key residues involved in binding are located in the strand regions delimiting the protein cavity, at the level of βD‐βJ strands, indicating that IRG is hosted in the protein internal cavity.…”
Section: Resultsmentioning
confidence: 99%
“…Much work has been then devoted to unravel the mechanism of allostery, describing the structural determinants of ligand binding and evaluating the role of protein dynamics in ligand recognition [30, 31, 36]. Specifically one highly conserved buried histidine (H98) was indicated to play a central role in establishing a network of hydrogen bonds and salt bridges among buried residues, defining a sort of continuous polar ‘‘spine’’ connecting remote strands of the liver apo protein (Figure 2) [20, 32]. Indeed a mutation of H98 was shown to disrupt the energetic communication functional to efficient binding [29].…”
Section: Babp As Host Of Endogenous Ligands: Bile Acid Poolmentioning
confidence: 99%
“…It was shown that when the human ileal protein is incubated with a mixture of the two bile salts, GCA binds nearly exclusively to one site, while GCDA binds nearly exclusively to the other site [33]. In the case of the chicken liver scaffold, the presence of a disulphide bridge was required to confer site selectivity to the protein [20]. Indeed sequence analysis of non-mammalian chicken liver BABP (access code P80226 in Swiss-Prot) reported the presence of a cysteine residue at position 80 and of a threonine residue at position 91.…”
Section: Babp As Host Of Endogenous Ligands: Bile Acid Poolmentioning
confidence: 99%
See 2 more Smart Citations